# 0.19x+0.4(x-3)=0.01(4x-5)

## Simple and best practice solution for 0.19x+0.4(x-3)=0.01(4x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 0.19x+0.4(x-3)=0.01(4x-5) equation:

0.19x+0.4(x-3)=0.01(4x-5)
We move all terms to the left:
0.19x+0.4(x-3)-(0.01(4x-5))=0
We multiply parentheses
0.19x+0.4x-(0.01(4x-5))-1.2=0

We calculate terms in parentheses: -(0.01(4x-5)), so:
0.01(4x-5)
We multiply parentheses
0.04x-0.05
Back to the equation:
-(0.04x-0.05)

We add all the numbers together, and all the variables
0.59x-(0.04x-0.05)-1.2=0
We get rid of parentheses
0.59x-0.04x+0.05-1.2=0
We add all the numbers together, and all the variables
0.55x-1.15=0
We move all terms containing x to the left, all other terms to the right
0.55x=1.15
x=1.15/0.55
x=2+0.05/0.55

`